Effectiveness of PEHRs use to increase vaccine uptake: a systematic review. (30th September 2020) - Balzarini, F; Oradini Alacreu, A; Frascella, B; Gaetti, G; Signorelli, C; Odone, A
Abstract: Background: The digital transformation provides tools to empower individuals and enable feedback and interaction between users and healthcare providers. Although Personal Electronic Health Records (PEHR) have been identified as innovative tools enabling the provision of patient-centered care and prevention, evidence on their impact is scant. Methods: We conducted a systematic review following the PRISMA guidelines to retrieve, quantitatively pool and critically appraise the effectiveness of PEHR access on vaccine uptake. Analysis on effectiveness were carried out for the following comparison strata: i) PEHR access vs no intervention, ii) PEHR access vs access with additional features. Results: Of identified 3125 citations, 8 studies were included, the majority published in the US before 2015. Four studies assessed differences between subjects with and without access to PEHR. Access to PEHR was reported to be an effective tool to increase vaccine uptake: when accessing PEHR, study participants were 6.7% more likely to receive influenza vaccine, parents to have children vaccinated, lifetime pneumococcal vaccination was reported to be higher in diabetic patients, a positive impact on preventive behaviors was reported. Four included studies reported on the effect of access to PEHR with or without additional communication features. In one study, the effect of electronic messages delivered through PEHRs wasn't differentially distributed in the arm receiving tailored messages on influenza, and in the arm receiving educational messages on other diseases. In other studies, active PEHR users were more likely to be vaccinated against influenza and Herpes Zoster, subjects who in addition received reminders had higher rates of influenza vaccination. Conclusions: While immunization programs are struggling to achieve optimal coverage targets, our findings can partially outline the association between PEHR access and vaccine uptake and further experimental research is needed. Key messages: PEHRs offer great potential to support population health and in particular immunization programs, helping to put people and patients at the center of care delivery, supporting patient empowerment. Although our findings suggest immunization coverage might benefit from people accessing PEHR, there is an urgent need to produce solid experimental evidence to quantify such effect.